Hubungan Pengetahuan dan Sikap Ibu Hamil Dengan Kepatuhan Mengkomsumsi Tablet Tambah Darah di RSUD Balaraja Tahun 2025 - Marina Marina; Omsah Omsah; Sri Ayu Wulandari; Yulie Novadianty Santoso; Lia Setiawati (Universitas Pahlawan Tuanku Tambusai, 2025)
Anemia in pregnant women is still a significant health problem in Indonesia with a prevalence reaching 48.9% in 2022. The Indonesian government has provided 90 Iron and Folic Acid Tablets (IFAT) during pregnancy to prevent anemia. Adherence of pregnant women to consuming IFAT is influenced by several factors, one of which is knowledge and attitude. The general objective of this study is to determine the relationship between the knowledge and attitudes of pregnant women and their adherence to consuming IFAT at Balaraja Hospital in 2025. This study uses a cross-sectional design with a quantitative approach. The research was conducted at Balaraja Hospital in May 2025. The study population was all pregnant women in the first, second, and third trimesters. Sampling was done by non-probability sampling with the accidental sampling method. Data was collected through a questionnaire. The results show that there is a significant relationship between knowledge and adherence to IFAT consumption with a p-value of 0.000 < α 0.005. In addition, there is also a significant relationship between the attitude of pregnant women and their adherence to consuming IFAT with a ρ Value of 0.000 < α 0.005. There is a relationship between the knowledge and attitudes of pregnant women and their adherence to consuming iron and folic acid tablets at Balaraja Hospital in 2025